Khazars, Kipchaks, Burtas: On the Ethnic Ancestors of the Nizhnii Novgorod Mishar Tatars. Issue 4 (2nd October 2018) - Khairetdinov, Damir Z.
Abstract : The Nizhnii Novgorod Mishar Tatars (the Nizhgars) are one of the specific groups of the Tatar people. Emerging not only, and not so much, based on religion, they represent a subethnos with its own ethnogenetic, linguistic, and cultural specifics. The Nizhgars differ from other Tatar subethnoses by a particular worldview, Mishar dialect, and rather strict marital endogamy, which continued until the 1960s. The origin of the Mishar Tatars is a controversial question that has not been resolved, due partly to sparse relevant research. Besides Turkified Madzhar-Ugrians (Mozhars), researchers have suggested Khazars, Kipchaks, and Burtas among their ancestors from the pre-Mongol period. The present article explores some of these hypotheses.